2014
DOI: 10.5012/bkcs.2014.35.4.1098
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Donor-Acceptor-Acceptor-Acceptor Polymer Containing Benzodithiophene and Benzimidazole-Benzothiadiazole-Benzimidazole for PSCs

Abstract: New electron deficient acceptor-acceptor-acceptor type of monomer unit composed of weak electron accepting benzimidazole and relatively strong electron accepting benzothiadiazole derivatives namely 4,7-bis(6-bromo- The opto-electrical studies revealed that the absorption band of PBDTBBB appeared in the range of 300 nm-525 nm and its highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels were positioned at −5.18 eV and −2.84 eV, respectively. The power conversion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Earlier reports conrmed that the incorporation of sterically hindered electron donor groups, such as 3octylthiophene or alkoxy benzene, or an electron accepting benzimidazole derivative on both sides of the BT restrict the ICT from the donor to the acceptor units when they are polymerized with electron-rich units. 15,17,23,34 These results suggest that the incorporation of Oxa units on both sides of the BT unit also diminish the ICT between the D-A units. The absorption onset wavelengths of P(BDT-BBOB) and P(BDT-BOB) were calculated to be 534 nm and 622 nm, respectively, from which the optical band gaps (E g,opt ) were determined to be 2.32 eV and 1.99 eV, respectively.…”
Section: Polymermentioning
confidence: 79%
See 1 more Smart Citation
“…Earlier reports conrmed that the incorporation of sterically hindered electron donor groups, such as 3octylthiophene or alkoxy benzene, or an electron accepting benzimidazole derivative on both sides of the BT restrict the ICT from the donor to the acceptor units when they are polymerized with electron-rich units. 15,17,23,34 These results suggest that the incorporation of Oxa units on both sides of the BT unit also diminish the ICT between the D-A units. The absorption onset wavelengths of P(BDT-BBOB) and P(BDT-BOB) were calculated to be 534 nm and 622 nm, respectively, from which the optical band gaps (E g,opt ) were determined to be 2.32 eV and 1.99 eV, respectively.…”
Section: Polymermentioning
confidence: 79%
“…8 Consequently, many studies have shown that the photovoltaic properties of the polymers incorporating BT-based acceptor units can be tuned via the incorporation/insertion of electron donating or accepting units on the BT moiety. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] In most of the studies, electron donating units, [15][16][17][18][19][20][21] such as benzene, thiophene, thienothiophene, and furan derivatives, are covalently attached on both sides of the BT unit or electron-rich alkoxy, 20,21 or electron-attracting uorides 8,28 are inserted on the back bone of the BT unit with the aim being to improve the absorption and carrier mobility and to tune the energy levels of the BT-based polymers. In addition, electron accepting units, such as thiazole 22 and benzimidazole, 23 are also attached on both sides of the BT units or quinoxaline, 24,25 and thiadiazole 26 and N-alkylpyrrolidine-2,5-dione rings 27 are fused on the BT back bone with the aim being to increase the electron attracting ability of the BT unit.…”
Section: Introductionmentioning
confidence: 99%
“…The building units of TPBD and BTDD were synthesised according to the reported methods with slight modifications (see in Supporting Information) 39,40 . The 2D COF was prepared as follows: after dissolving TPBD and BTDD in a mixed solvent of 1,2-dichlorobenzene:n-butanol (v:v = 1:1) and ultrasonicating 20 min to generate a dark purple solution, acetic acid (6 M) was added, followed by rapid freezing to 77 K, degassed through three cycles of freeze-pump-thaw, and sealed under vacuum.…”
Section: Cof Design and Synthesismentioning
confidence: 99%
“…5). The non-local density function theory [31][32][33][34][35][36][37][38][39][40][41][42] was employed to estimate a pore size distribution of~1.8 nm (Supplementary Fig. 5).…”
Section: Cof Design and Synthesismentioning
confidence: 99%
See 1 more Smart Citation